2014
DOI: 10.1371/journal.pone.0088063
|View full text |Cite
|
Sign up to set email alerts
|

Association between Amylin and Amyloid-β Peptides in Plasma in the Context of Apolipoprotein E4 Allele

Abstract: Amylin, a pancreatic peptide that readily crosses the blood brain barrier (BBB), and amyloid-beta peptide (Aβ), the main component of amyloid plaques and a major component of Alzheimer's disease (AD) pathology in the brain, share several features. These include having similar β-sheet secondary structures, binding to the same receptor, and being degraded by the same protease. Thus, amylin may be associated with Aβ, but the nature of their relationship remains unclear. In this study, we used human samples to stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 45 publications
(54 reference statements)
0
13
0
Order By: Relevance
“…The differences between the conformational properties of toxic h-IAPP oligomers defined in the present work and those recently identified for Aβ are particularly interesting, given that the two polypeptides share important features and given the growing evidence that links T2D and AD ( Yang and Song, 2013 ; Oskarsson et al, 2015 ; Ninomiya, 2014 ). Pre-fibrillar forms of h-IAPP and Aβ interact in vitro and a positive association has recently been demonstrated in plasma ( Miklossy et al, 2010 ; Qiu et al, 2014 ). Furthermore, Aβ can seed amyloid formation by h-IAPP in vitro and Aβ has been reported to form pancreatic deposits in T2D, while h-IAPP has been reported in brain plaques in AD ( O'Nuallain et al, 2004 ; Oskarsson et al, 2015 ; Miklossy et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…The differences between the conformational properties of toxic h-IAPP oligomers defined in the present work and those recently identified for Aβ are particularly interesting, given that the two polypeptides share important features and given the growing evidence that links T2D and AD ( Yang and Song, 2013 ; Oskarsson et al, 2015 ; Ninomiya, 2014 ). Pre-fibrillar forms of h-IAPP and Aβ interact in vitro and a positive association has recently been demonstrated in plasma ( Miklossy et al, 2010 ; Qiu et al, 2014 ). Furthermore, Aβ can seed amyloid formation by h-IAPP in vitro and Aβ has been reported to form pancreatic deposits in T2D, while h-IAPP has been reported in brain plaques in AD ( O'Nuallain et al, 2004 ; Oskarsson et al, 2015 ; Miklossy et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our recent study found that amylin was associated with Aβ in plasma. However, in the presence of ApoE4, the association between amylin and Aβ 1–40 disappeared [34]. ApoE4 may either block or attenuate amylin’s effect on blood vessels in the brain that leads to cognitive decline.…”
Section: Discussionmentioning
confidence: 99%
“…A translational study using human subjects demonstrates that a single injection of pramlintide, an amylin analog, similarly induced a surge of Aβ in plasma in AD patients (Zhu et al, 2017a). Amylin and Aβ have consistently been positively associated in plasma in humans (Qiu et al, 2014), suggesting that the more amylin in blood crossing the BBB, the more Aβ moved out of the brain into the blood.…”
Section: Amylin Treatment Reduces the Core Ad Pathology In Ad Mouse Mmentioning
confidence: 99%